Systematic Literature Review Tentang Pengaruh Media Pembelajaran Interaktif Terhadap Keterlibatan Mahasiswa - Selvia Rusika; Agus Lestari (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
The rapid development of information technology demands the integration of interactive learning media in higher education to enhance student engagement. This study employs a Systematic Literature Review (SLR) to synthesize the effects of interactive media on students’ motivation, participation, and learning outcomes. The SLR process followed four stages: identification, screening, eligibility, and inclusion. A total of 20 articles were retrieved from Google Scholar (2019–2025) using keywords related to interactive media and student engagement. During title and abstract screening, 5 articles were excluded for irrelevance, leaving 15 eligible studies that were fully reviewed and included in the analysis. The synthesis reveals that interactive media enhance student engagement through three effectiveness categories: fast-motivation media (TikTok), competitive-participation media (Quizizz), and immersive-experience media (VR, AI). However, their effectiveness is influenced by infrastructure limitations and educators’ competencies. These findings reinforce engagement theory and Constructivism within digital learning contexts. Keywords: Interactive Learning Media; Student Engagement; Systematic Literature Review; Learning Motivation; Educational Technology. Abstrak Perkembangan teknologi informasi menuntut hadirnya media pembelajaran interaktif di perguruan tinggi untuk meningkatkan keterlibatan mahasiswa. Penelitian ini menggunakan Systematic Literature Review (SLR) guna mensintesis pengaruh media interaktif terhadap motivasi, partisipasi, dan hasil belajar. Proses SLR dilakukan melalui empat tahap: identifikasi, penyaringan, kelayakan, dan inklusi. Sebanyak 20 artikel ditemukan melalui Google Scholar (2019–2025) menggunakan kata kunci terkait media interaktif dan student engagement. Pada tahap penyaringan judul dan abstrak, 5 artikel dieliminasi karena tidak relevan, sehingga tersisa 15 artikel yang kemudian dinilai kelayakannya dan seluruhnya memenuhi kriteria untuk dianalisis. Hasil sintesis menunjukkan bahwa media interaktif meningkatkan keterlibatan mahasiswa melalui tiga kategori efektivitas: media motivasi cepat (TikTok), media partisipasi kompetitif (Quizizz), dan media pengalaman mendalam (VR, AI). Namun, efektivitasnya dipengaruhi keterbatasan infrastruktur dan kompetensi pendidik. Temuan ini memperkuat teori keterlibatan dan Konstruktivisme dalam konteks pembelajaran digital. Kata Kunci: Media Pembelajaran Interaktif; Keterlibatan Mahasiswa; SLR; Motivasi Belajar; Teknologi Pendidikan.